Mergeable adaptive tile coding method - Meng-yu SHI; Quan LIU; Qi-ming FU (Tongxin xuebao)
In order to solve many unnecessary division,mergence supported adaptive tile coding algorithm was presented which would eliminate the unnecessary division.Simulation is conducted on mountain car problem with discrete actions and continuous state space Results show that the proposed method can eliminate the influence of false division in the traditional tile coding method and achieve a more accurate adaptive partition of continuous state space.A higher convergence rate is achieved at the same time.